2000
DOI: 10.1002/ir.10703
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Tasks on the Path to College for America's Disadvantaged

Abstract: Using data from the National Educational Longitudinal Study of 1988, this chapter seeks to gain a better understanding of what factors assist economically and sociologically underprivileged Americans to ready themselves for college.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 11 publications
2
50
1
Order By: Relevance
“…Based on their review and synthesis of prior research, Cabrera and La Nasa (2000) concluded that parental encouragement may be manifested via high expectations for the students' degree attainment, a motivational form of encouragement, and via particular activities, a proactive form of encouragement. Proactive activities may include parental involvement in school activities and processes, parental saving for college, and parentstudent discussions about college and education-related topics.…”
Section: Parental Involvement In College Going 565mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on their review and synthesis of prior research, Cabrera and La Nasa (2000) concluded that parental encouragement may be manifested via high expectations for the students' degree attainment, a motivational form of encouragement, and via particular activities, a proactive form of encouragement. Proactive activities may include parental involvement in school activities and processes, parental saving for college, and parentstudent discussions about college and education-related topics.…”
Section: Parental Involvement In College Going 565mentioning
confidence: 99%
“…As suggested in prior research (Cabrera & La Nasa, 2000;Perna & Titus, 2005), parents shape college opportunity for their children in a variety of ways. Participants indicate that parents support and encourage college opportunity through their expectations for their children's educational and occupational attainment, discussions with their children about college-related activities, efforts to take their children to visit colleges, and ability and willingness to pay college prices.…”
Section: Parents Shape College Opportunity For Their Children But Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The path of a successful PSE requires that students gain access to an institution of higher education, negotiate the process of PSE, and complete curriculum that supports their career objectives (Cabrera & LaNasa, 2000;Schneider & Stevenson, 1999;Venezia & Jaeger, 2013).…”
mentioning
confidence: 99%
“…Researchers have found that parental involvement is associated with a greater likelihood of aspiring to attend college and actually enrolling (Cabrera & La Nasa, 2000;Horn, 1998;Hossler, Braxton & Coopersmith, 1989;Hossler, Schmit & Vesper, 1999;Perna, 2000), as well as with higher grades (Lee, 1993;Muller, 1993;Zick, Bryant, & Osterbacka, 2001), higher eighth grade mathematics and reading achievement (Lee, 1993;Sui-Chu & Willms, 1996), lower rates of behavioral problems (Lee, 1993;Zick, Bryant, & Osterbacka, 2001), and lower likelihood of high school dropout and truancy (McNeal, 1999).…”
mentioning
confidence: 99%